EXPOSURE EFFECT OF MAGNETIC FIELD ON WATER PROPERTIES IN RECIRCULATION AQUACULTURE SYSTEMS(RAS) - & et al., Hassan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The objective of this study to investigate the effect of magnetic field on water properties recirculating aquaculture systems. This study is based on previous works reporting the positive effects of exposure to magnetic field on water properties, plant growth, plant germination, livestock-drinking water, and fish fertilisation. It was conducted against the backdrop of serious issues pertaining to water quality in recirculating aquaculture systems, which negatively impact aquaculture species growth. First, this work evaluates the effect of exposed to magnetic field intensities of 0.10, 0.15, 0.20, 0.10+0.15, 0.10+0.20, 0.15+0.20, and 0.10+0.15+0.20 T on water quality. The results showed significant (p < 0.05) increases of the dissolved oxygen (DO), pH, and conductivity(CD) by 17.3, 1.6, 3.0%, respectively, and significant decreases of the ammonium level(NH4-N), specific conductivity(SPC), total dissolved solids(TDS), oxygen reduction potential(ORP), and chlorides by 25.3, 1.1, 1.4, 1.0, 16.9, 3.4%, respectively, throughout the experiment in recirculation aquaculture systems. Therefore, the installation of the device in recirculation aquaculture systems is simple, low cost, and can be retrofitted into existing systems, which helps simplify fish rearing for fish farmers.